CHARACTER EDUCATION ACCORDING TO IMAM AN- NAWAWI IN THE HADITH OF AL- ARBA’IN AND THE PERSPECTIVE OF ISLAMIC SCHOLARS - Nurul Widayanti (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Allah created Prophet Adam (peace be upon him) not without purpose or intention. It was not merely to make the earth more vibrant, but the primary purpose was to appoint Adam (peace be upon him) as a khalifah—a leader on earth. The role of a leader is to organize, manage, protect, preserve, and utilize all the resources that Allah has provided on this earth for the benefit and well-being of humankind. To fulfill his responsibilities as a leader, Allah prepared and equipped Adam (peace be upon him) with intellect and knowledge . In Surah At-Tin, verse 4, Allah explains: "Indeed, We created man in the best of stature," which means that Allah created humans in the most perfect form, endowed with intellect. With this intellect, humans are able to explore all of their potential for the benefit of humanity.